Fifty years of pancreatic islet pathology in human type 1 diabetes: insights gained and progress made - Morgan, Noel G. (Diabetologia, 2018)
Type 1 diabetes is increasing in incidence in many parts of the world and it might be imagined that the pathological processes that underlie disease progression are firmly understood. However, this is not the case; rather, our collective understanding is still surprisingly rudimentary. There are various reasons for this but one of the most important is that the target organ (the pancreas) has been examined at, or soon after, diagnosis in only a small number of cases worldwide over the past half a century. This review provides a summary of some of the insights gained from these studies and highlights areas of ongoing uncertainty. In particular, it considers the process of insulitis (a form of islet inflammation that occurs characteristically in type 1 diabetes) and discusses the factors that may influence the access of immune cells to the beta cells. Attention is also drawn to recent evidence implying that two distinct profiles of insulitis exist, which occur differentially in people who develop type 1 diabetes at increasing ages. Emphasis is also placed on the emerging (and somewhat surprising) consensus that the extent of beta cell loss is variable among people with type 1 diabetes and that many (especially those who are older at onset) retain significant numbers of insulin-producing cells long after diagnosis. We conclude by emphasising the importance of renewed efforts to study the human pancreas at disease onset and consider how the current insights may inform the design of future strategies to slow or halt the rate of beta cell loss. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-018-4731-y) contains a slideset of the figures for download, which is available to authorised users.